Time-series benthic community composition and biomass and associated environmental characteristics in the Chukchi Sea during the RUSALCA 2004–2012 program - Grebmeier, Jacqueline M.; Bluhm, Bodil; Cooper, Lee W.; Denisenko, Stanislav G.; Iken, Katrin; Kedra, Monika; Serratos, Carlos (Oceanography, 2015)
Published version also available at http://dx.doi.org/10.5670/oceanog.2015.61 Benthic macrofaunal and epifaunal composition and biomass and associated environmental drivers were evaluated for time-series stations occupied during three cruises of the RUSALCA (Russian-American Long-term Census of the Arctic) program undertaken in August 2004, September 2009, and September 2012. We focus on the benthic communities collected at repeat stations in the southern Chukchi Sea and the key environmental characteristics that could influence benthic population structure and biomass. These characteristics included bottom water temperature, salinity, and chlorophyll a (chl a); integrated chl a; export production via sediment oxygen uptake rates as an indicator of food supply to the benthos; and surface sediment parameters that are known to influence benthic population community composition and biomass, such as grain size, carbon content, and chl a. Overall, both the macrofaunal and epibenthic community composition at the time-series sites in the southern Chukchi Sea have remained relatively constant over the time period of this study (2004–2012). However, some of the more sedentary macrofauna are showing significant declines in biomass since 2004, particularly in the center of a macrobenthic hotpot that has been persistent for decades in the southern Chukchi Sea. While biomass estimates were more variable for the more motile epibenthic fauna, there was also an indication of declining epifaunal biomass since 2009. We highlight here as a case study the benthic time-series efforts during RUSALCA that are also part of the Distributed Biological Observatory (DBO) international network, which is tracking the status and trends of Arctic ecosystem response to the changing physical drivers in the southern Chukchi Sea.